Feeding Faba Beans (Vicia faba L.) Reduces Myocyte Metabolic Activity in Grass Carp (Ctenopharyngodon idellus) - Tian, Jing-jing; Fu, Bing; Yu, Er-meng; Li, Yu-ping; Xia, Yun; Li, Zhi-fei; Zhang, Kai; Gong, Wang-bao; Yu, De-guang; Wang, Guang-jun; Xie, Jun (Frontiers in Physiology, 2020)
In this study, we aimed to explore the effects of faba bean (Vicia faba L.) on the energy metabolism of grass carp (Ctenopharyngodon idellus). A total of 180 fish ( 2900 g) were randomly assigned to six tanks (2.5 × 2.5 × 1.2 m; 30 individuals per tank) and fed either faba bean (Vicia faba L.) or a commercial diet for 120 days (3% body weight, twice per day). The results showed that faba bean-fed grass carp (FBFG) had significantly lower growth and higher fat accumulation in the mesenteric adipose tissue and hepatopancreas than commercial diet-fed grass carp (CDFG). Compared with CDFG, FBFG exhibited no significant difference in proximate composition of the muscle; however, an obvious decrease in muscle fiber size and significantly higher hardness, chewiness, and gumminess were observed. Transcriptome results showed that a total of 197 genes were differentially regulated in the dorsal muscle. Down-regulated genes included four genes annotated with myocyte development and 12 transcripts annotated with components of myofibrils. In addition, the FBFG group exhibited significantly lower expression of genes associated with oxygen transport, the mitochondrial respiratory chain, and creatine metabolism, suggesting reduced energy availability in the muscle of the FBFG. Moreover, using western-blotting and enzyme assays, we found decreased protein levels in the mitochondrial electron transport respiratory chain and creatine metabolism activities, as well as increased expression of autophagy marker protein levels, in the muscle of FBFG. Overall, our results suggest that an abnormal energy distribution may exist in grass carps after feeding with faba bean, which is reflected by a mass of fat deposition in the adipose tissue and hepatopancreas and subdued metabolic activity in the muscle.